INCREASING FUTURE ENGINEERS’ MOTIVATION FOR ACQUIRING ENGLISH LANGUAGE PROFESSIONAL COMMUNICATIVE COMPETENCE - Saienko, Nataliia; Ptushka, Anastasiia; Baibekova, Liudmyla; Ilienko, Olena; Bogdan, Zhanna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Modern engineers have to constantly upgrade their knowledge and skills to stay relevant in today’s rapidly developing world and to establish professional ties with counterparts from other countries. It can hardly be done without knowledge of English as a dominant language of science and technology. Foreign language teachers in Ukraine and many other countries face the problem of improving technical students’ communicative competence to such a level that they could become full-fledged participants in intercultural professional communication. The problem can be solved provided that students have strong positive motivation for learning a foreign language. The aim of the study was to select and test a complex of methods to increase future engineers’ motivation for acquiring foreign language communicative competence. These methods included problem-solving, case study, web-quest, dilemma, round table, essay, audiovisual translation, etc. The effects of the tried-and-tested methods were compared to the results of a traditional teaching. The research was carried out at Kharkiv National Automobile and Highway University in 2021-2023 and aimed to compare 1) stability of students’ cognitive interest; 2) disclosure of creative potential; 3) development of language skills of two groups of learners: the experimental group and the control group. The results of the study indicate that the use of special methods to motivate students for language learning had a significant positive impact on future engineers’ communicative competence.